2019
DOI: 10.1111/1365-2745.13318
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of above‐ground understorey biomass and nutrient stocks in temperate deciduous forests

Abstract: 1. The understorey in temperate forests can play an important functional role, depending on its biomass and functional characteristics. While it is known that local soil and stand characteristics largely determine the biomass of the understorey, less is known about the role of global change. Global change can directly affect understorey biomass, but also indirectly by modifying the overstorey, local resource availability and growing conditions at the forest floor.2. In this observational study across Europe, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 106 publications
4
20
1
Order By: Relevance
“…Contrary to our third hypothesis, the quality of overstorey litter did not influence understorey biomass or its contribution to litter production. This again confirms that light availability is the main limiting resource for understorey productivity (Gilliam and Turrill 1993;Axmanová et al 2011;Smolko and Veselovská 2018;Landuyt et al 2019b). We did find a general positive relationship between overstorey litter quality (with a low C/N indicating a high litter quality) and understorey N concentration.…”
Section: The Main Drivers Of Understorey Litter Production and Nutriesupporting
confidence: 83%
See 2 more Smart Citations
“…Contrary to our third hypothesis, the quality of overstorey litter did not influence understorey biomass or its contribution to litter production. This again confirms that light availability is the main limiting resource for understorey productivity (Gilliam and Turrill 1993;Axmanová et al 2011;Smolko and Veselovská 2018;Landuyt et al 2019b). We did find a general positive relationship between overstorey litter quality (with a low C/N indicating a high litter quality) and understorey N concentration.…”
Section: The Main Drivers Of Understorey Litter Production and Nutriesupporting
confidence: 83%
“…This relationship was the strongest in mountainous beech forests. Mechanisms behind these relationships are probably related to soil nutrient availability, as found by Landuyt et al (2019b). High quality overstorey litter can increase soil nutrient availability, which promotes nutrient uptake by understorey plants.…”
Section: The Main Drivers Of Understorey Litter Production and Nutriementioning
confidence: 93%
See 1 more Smart Citation
“…In this study, no or only weak correlations were found between herb layer cover and other forest attributes such as over-and midstory tree and shrub vegetation, which were identified as important driver in relevant studies (e.g. Landuyt et al 2019b). This may be due to the typically heterogeneous forest structure in Switzerland (Thürig and Kaufmann 2010) preventing single attributes to become dominant drivers at the national scale of the NFI.…”
Section: Discussioncontrasting
confidence: 56%
“…As we currently lack information on how C-stocks are impacted by edge influences in Europe, we focused in this study on edge-tointerior gradients in three of the major C-pools (the aboveground biomass, forest floor and topsoil C-stock) along a latitudinal gradient. For feasibility reasons across 225 European forest plots, we did not consider other stocks such as the belowground living biomass stock (roots) or the stock in understorey herbs and very small shrubs and trees with a DBH below 7.5 m. These stocks, although they generally only represent less than 10% of C-stocks in forests (Vande Walle et al, 2001;Lal and Lorenz, 2012;Landuyt et al, 2019) might also be influenced by environmental changes near forest edges (Remy et al, 2016;Saeed et al, 2019). Considering these stocks in future research could nevertheless further contribute to filling this knowledge gap and improve our predictions on C-stocks near forest edges.…”
Section: Limitations and Opportunities For Future Researchmentioning
confidence: 99%